Flavonoids as Strong Inhibitors of MAPK3: A Computational Drug Discovery Approach - Amir Taherkhani; Parita Khodadadi; Lida Samie; Zahra Azadian; Zeynab Bayat (International Journal of Analytical Chemistry)
Background. Mitogen-activated protein kinase 3 (MAPK3) mediates the onset, progression, metastasis, drug resistance, and poor prognosis in various malignancies, including glioma, liver, ovarian, thyroid, lung, breast, gastric, and oral cancers. Negative regulation of MAPK3 expression using miRNAs has led to therapeutic effects in cancer. Objectives. The present study performed molecular docking and dynamics simulation to identify potential MAPK3 inhibitors from natural flavonoids, possibly leading to drug development in cancer therapy. Methods. A computational drug discovery approach was performed using the AutoDock tool to identify potential MAPK3 inhibitors from 46 plant-based flavonoids. A cross-validation study was executed using the Schrödinger Maestro docking tool. Molecular dynamics (MD) was executed to evaluate the stability of docked poses between the top-ranked compounds and the MAPK3 catalytic domain. Interactions among the most potent MAPK3 inhibitors and residues within the receptor’s active site were studied using the BIOVIA Discovery Studio Visualizer before and after 100 ns MD simulations. Results. Kaempferol 3-rutinoside-4′-glucoside, kaempferol 3-rutinoside-7-sophoroside, rutin, and vicenin-2 exhibited a magnificent binding affinity to the receptor’s active site. In addition, the stability of the docked poses of these compounds seemed to be stable after ∼45 ns computer simulations. Conclusion. The present study suggests that kaempferol 3-rutinoside-4′-glucoside, kaempferol 3-rutinoside-7-sophoroside, rutin, and vicenin-2 could strongly bind to the MAPK3 catalytic site and could be assigned as a potent inhibitor for MAPK3. These findings may be helpful in the treatment of various cancers. However, further validation experiments are needed.